2013
DOI: 10.1007/s00221-013-3604-3
|View full text |Cite
|
Sign up to set email alerts
|

Postural responses to electrical stimulation of the vestibular end organs in human subjects

Abstract: A multichannel vestibular prosthesis that delivers electrical stimulation to the perilymph of individual semicircular canals is a potential new treatment modality for patients with vestibular deficiencies. Most research in this field has evaluated the efficacy of this approach by its ability to reproduce eye movements in response to head rotations. Our group has developed such a device and implanted it in four human subjects with intractable unilateral Meniere's disease. This allows us to evaluate individual s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
47
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(50 citation statements)
references
References 52 publications
0
47
0
3
Order By: Relevance
“…34, 35 Restoring the function of one labyrinth through gene therapy 36 , stem cell interventions 37 or prosthetic interventions 38–46 yield significant benefits. For example, a multi-channel vestibular prosthesis (MVP) currently in development may partly restore unilateral semicircular canal function to BVD patients, thereby improving vestibulo-ocular reflex performance, visual acuity during head movement and postural stability 38, 39, 43–46 . An important consideration in its development is the device’s cost-utility.…”
Section: Discussionmentioning
confidence: 99%
“…34, 35 Restoring the function of one labyrinth through gene therapy 36 , stem cell interventions 37 or prosthetic interventions 38–46 yield significant benefits. For example, a multi-channel vestibular prosthesis (MVP) currently in development may partly restore unilateral semicircular canal function to BVD patients, thereby improving vestibulo-ocular reflex performance, visual acuity during head movement and postural stability 38, 39, 43–46 . An important consideration in its development is the device’s cost-utility.…”
Section: Discussionmentioning
confidence: 99%
“…They fulfilled the following inclusion criteria: (1) mean peak slow phase velocity of 5°/s or less in bilateral bithermal (30 and 44°C) caloric irrigations with water, (2) pathologic head-impulse test for horizontal and vertical semicircular canals, and (3) a VOR gain of <0.25 on rotatory chair tests. In addition, since there is a non-negligible risk of inducing a profound hearing loss with the implantation surgery (5, 17, 19, 20), we chose patients who were also profoundly deaf in the implanted ear (i.e., and thus could benefit from a cochlear implant).…”
Section: Methodsmentioning
confidence: 99%
“…They have also conducted preliminary animal studies confirming the possibility to electrically elicit eye movements (and thus effectively activate the vestibular system) with their device, and suggested that it was possible to preserve hearing and pre-existing vestibular function after implantation (18). Unfortunately, this was not verified in humans and both the auditory and vestibular function of implanted patients deteriorated considerably (17, 19). Recently, this group shifted focus to a motion coding device, as mentioned in a recent publication exploring the possibility to induce body sway upon computer-controlled electrical stimulation (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, vestibular neurostimulators have been shown to be capable of producing aVOR-like nystagmus, the slow phase velocity of which can be controlled by modulating the current amplitude or pulse rate of the stimulation train and the direction by varying which canal nerves receive stimulation. Further studies have demonstrated that such a stimulator, combined with a headmounted rotational sensor, constitutes a functional vestibular prosthesis that is capable of partially restoring vestibulo-ocular reflex (VOR) Perez Fornos et al 2014;Golub et al 2014;Guyot et al 2011aGuyot et al , b, 2012Pelizzone et al 2014;Phillips et al 2015a, b;Thompson et al 2012;Wall et al 2007), producing head and postural movements (Mitchell et al 2013;Phillips et al 2013), and eliciting perceptual responses (Lewis et al 2013, Phillips et al 2015a.…”
Section: Introductionmentioning
confidence: 99%